Study on bearing capacity of Mortise-tenon and joint-flange concrete assembled foundation of transmission line under combined load. - Xin Hu; Xiaojuan Xi; Yuesong Zheng; Zijun Xiang; Han Zhang (PLoS ONE)
Mortise-tenon and joint-flange assembled foundation has excellent application as a new type of slab concrete assembled foundation, but there is a lack of research on its bearing capacity. In order to explore the mechanical characteristics and bearing capacity of this type of foundation under combined load (uplift-horizontal load), which is different from the traditional cast-in-place foundation, the uplift bearing model of mortise-tenon and joint-flange assembled foundation and the uplift model of cast-in-place foundation with the same specification were established based on the actual geological environment by finite element software. The stress distribution, vertical and horizontal displacements, and uplift and horizontal bearing capacities of the foundations were simulated and calculated. This study found that the bearing capacity of the Mortise-tenon and joint-flange assembled foundation has not been fully utilized. Specifically, the deformation of the foundation mainly concentrates on the main column, and the load is unable to be transmitted to the lower structure through the flange. Under combined loading (uplift-horizontal load), the load-displacement relationship curve can be roughly divided into three stages: linear slow rise stage, plastic accelerated rise stage, and linear failure stage. During the pull-out process, the foundation demonstrates stress characteristics of segmented load transmission. After the concrete upper column yields, the mortise-tenon and joint-flange connection node receives the load transmitted by the upper column, and continues to transmit the load to the lower column of the foundation after the displacement of the node reaches its limit. When the uplift cumulative displacement of the foundation reaches approximately 13 mm and the horizontal cumulative displacement reaches around 10 mm, the foundation reaches its ultimate state. At this point, its ultimate bearing capacity surpasses that of the cast-in-place foundation of the same specification, with significant improvement. The ultimate uplift bearing capacity increases by 33.34%, while the ultimate horizontal bearing capacity increases by 48.09%.